Synonyms for some species of Mexican anoles (Squamata: Dactyloidae) - de Oca, Adrián Nieto Montes; Poe, Steven; Scarpetta, Simon; Gray, Levi; Lieb, Carl S. (Zootaxa, 2013)
We studied type material and freshly collected topotypical specimens to assess the taxonomic status of five names asso-ciated with species of Mexican Anolis. We find A. schmidti to be a junior synonym of A. nebulosus, A. breedlovei to be a junior synonym of A. cuprinus, A. polyrhachis to be a junior synonym of A. rubiginosus, A. simmonsi to be a junior syn-onym of A. nebuloides, and A. adleri to be a junior synonym of A. liogaster.